Recovery Potential of Cold Press Byproducts Obtained from the Edible Oil Industry: Physicochemical, Bioactive, and Antimicrobial Properties - Karaman, Safa; Karasu, Salih; Tornuk, Fatih; Toker, Omer Said; Gecgel, Umit; Sagdic, Osman; Ozcan, Nihat; Gul, Osman (AMER CHEMICAL SOC, 2015)
Physicochemical, bioactive, and antimicrobial properties of different cold press edible oil byproducts (almond (AOB), walnut (WOB), pomegranate (POB), and grape (GOB)) were investigated. Oil, protein, and crude fiber content of the byproducts were found between 4.82 and 12.57%, between 9.38 and 49.05%, and between 5.87 and 45.83%, respectively. GOB had very high crude fiber content; therefore, it may have potential for use as a new dietary fiber source in the food industry. As GOB, POB, and WOB oils were rich in polyunsaturated fatty acids, AOB was rich in monounsaturated fatty acids. Oil byproducts were also found to be rich in dietary mineral contents, especially potassium, calcium, phosphorus, and magnesium. WOB had highest total phenolic (802 ppm), flavonoid (216 ppm), and total hydrolyzed tannin (2185 ppm) contents among the other byproducts. Volatile compounds of all the byproducts are mainly composed of terpenes in concentration of approximately 95%. Limonene was the dominant volatile compound in all of the byproducts. Almond and pomegranate byproduct extracts showed antibacterial activity depending on their concentration, whereas those of walnut and grape byproducts showed no antibacterial activity against any pathogenic bacteria tested. According to the results of the present study, walnut, almond, pomegranate, and grape seed oil byproducts possess valuable properties that can be taken into consideration for improvement of nutritional and functional properties of many food products.
Keywords: almond; grape; pomegranate; walnut; cold press oil; byproducts; TOTAL PHENOLIC CONTENTS; TOTAL LIPID-CONTENT; ANTIBACTERIAL ACTIVITIES; GRAPE VARIETIES; POLYPHENOLS; FLAVONOIDS; EXTRACTS; PROFILE; OILSEED; SEEDS; Agriculture; Chemistry; Food Science & Technology